The Meaning of Pancasila in Civil Society Movements for Strengthening Democracy - M. Nawawi; Ellena Lee; Rifqi Muhammad Firdaus; Muafi (Jurnal Pelita Raya, 2025)
In a democratic arena increasingly vulnerable to being hijacked by empty slogans, identity politics, and repression disguised as order, this study critically examines how civil society movements reinterpret Pancasila as a source of moral legitimacy and a practical strategy for reclaiming freedom, testing the accountability of power, and upholding equal rights for citizens as the core of substantive democracy. This study is an interdisciplinary qualitative case study grounded in a multi-perspective approach that combines democracy and social movement theory and is complemented by the lens of hegemony-legitimacy and discourse theory. The results state that Pancasila will not save democracy if it continues to be treated as a mantra of unity that is sterile from conflict, because in an ecosystem of political identity, closed bureaucracy, and digital propaganda, Pancasila is easily hijacked and used as a moral stamp to justify silencing, discrimination, and impunity. Therefore, strengthening democracy requires the activation of Pancasila as an ethical weapon that can be enforced rather than sacralised through concrete indicators of official behaviour, as well as a counter-narrative language capable of subduing hate speech and disinformation through the production of short content, testimonials from local figures, and micro-influencer networks that transform national pride into a commitment to human rights.